Split nitrogen applications provide no benefit over a single well timed application in rainfed winter wheat - Abiola, Samson Olaniyi; Bigatao Souza, Joao Luis; Sharry, Raedan; Derrick, Jolee R.; Maatougui, Meryem; Arnall, Daryl Brian (Frontiers in Plant Science, 2025)
Optimizing nitrogen (N) fertilization strategies in winter wheat requires understanding the combination of application timings and rates. This is crucial for achieving the dual objectives of maximizing grain yield while maintaining adequate grain protein concentration (GPC). Research has been conducted in central Great Plains to document the value of a single delayed application on N. However, most of this work was performed at sub-optimum N rates, and without a comparison with split application. This study evaluated N fertilization across multiple site-years to identify optimal timing of split applications and single applications under sub-optimum and excessive N rates. Field experiments were conducted at three locations in Oklahoma across three growing seasons (2018-2021), testing two N rates (100 and 200 kg N ha⁻¹) applied at five timing intervals based on growing degree days (0, 30, 60, 90, and 120 GDD). The split application received 50 kg pre- and 50 kg in season. The 100 kg rate was chosen to represent sub-optimum, while the 200 kg rate was in excess. The 100 kg N ha⁻¹ achieved grain yields of 5.0 Mg ha⁻¹, statistically similar to 200 kg N ha⁻¹ (5.1 Mg ha⁻¹) across all application timings, but GPC was increased at all timings except 120 GDD. These results confirm that 100 kg N ha⁻¹ was sub-optimum for protein but adequate for yield, while 200 kg N ha⁻¹ was excessive for yield but achieved premium protein. Application timing significantly influenced both yield and GPC, with 90 GDD applications producing optimal yields (5.4 Mg ha⁻¹) and adequate protein levels (12.5% GPC). In-season applications at 30–90 GDD achieved 12% higher GPC compared to pre-plant applications, while maintaining equivalent yields at 11.6%. Early applications (0–90 GDD) sustained maximum yield potential. Late applications (120 GDD) increased GPC by 1.2%. In-season applications aligned with crop demand periods which could potentially reduce operational costs and time compared to split applications by eliminating the need for multiple tractor operations. These results demonstrate the importance of strategic timing over increased N rates for achieving sustainable wheat production that balances high yields, adequate protein levels, and efficient N use while minimizing environmental impacts.